Validation of an instrument to assess knowledge, attitudes, and practices regarding occupational accident prevention among rice farmers - My Ha Nguyen; Toan Van Ngo; Linh Gia Vu; Dat Cong Truong; Hai Minh Vu (PLoS ONE, 2025)
Background Despite the hazardous nature of rice farming, limited evidence exists regarding farmers’ knowledge, attitudes, and practices (KAP) toward accident prevention, and no standardized instrument is currently available to measure these dimensions in Vietnam or comparable contexts. This study aimed to develop and validate a psychometrically sound instrument for assessing rice farmers’ KAP related to occupational accident prevention. Methods Instrument development and validation were carried out in three stages. First, an initial item pool was generated through an extensive review of existing literature. Second, content validity was established through expert consultation involving professionals in agriculture, occupational health, and public health. Third, a pilot study was conducted with 168 rice farmers in Thai Binh Province, Vietnam, to evaluate the instrument’s psychometric properties. Results Exploratory factor analysis identified 20 items across five factors in the knowledge domain, nine items forming a single factor for attitudes, and 17 items grouped into four factors for practices, explaining 85.8%, 43.8%, and 72.3% of the total variance, respectively. Confirmatory factor analysis supported these structures, demonstrating satisfactory model fit across domains. The instrument exhibited high internal consistency, with Cronbach’s alpha values ranging from 0.894 to 0.969 for knowledge, 0.833 for attitudes, and 0.805 to 0.933 for practices. Conclusion The validated instrument provides a reliable and valid measure of rice farmers’ knowledge, attitudes, and practices concerning occupational accident prevention. It offers a robust foundation for future research, monitoring, and targeted interventions aimed at improving safety behaviors and reducing injury risks among agricultural workers.